HUMAN RESOURCE MANAGEMENT AFFECTING COMPETENCIES OF TEACHERS IN PRIVATE SCHOOLS UNDER SAMUTPRAKAN PROVINCIAL EDUCATION OFFICE - Charoenhiruntorn, Washirasak; Phutiariyawat, Jantarat (Journal of Social Science and Cultural, 2024)
The objectives of this research were as follows: 1) To study the level of human resource management and competencies of teachers in private school; 2) To study the relationship of human resource management and competencies of teachers in private school and; and 3) To identify human resource management affecting competencies of teachers in private schools. The samples were 357 people, including teachers in private schools under the Samutprakan provincial education office, and selected by cluster random sampling. The research instrument was a Likert scale questionnaire comprised of five levels rating scale, which was examined for content validity by experts. The Index of Item-Objective Congruence was obtained between 0.60 - 1.00 and the questionnaire’s reliability was 0.963. The data were analyzed using descriptive statistics and multiple regression analysis-enter method. The findings were as follows: 1) The level of human resource management of private schools administrators were at a highest level with the mean level from highest to lowest as follows: human resource planning, personnel relationship, work evaluation, personnel development, renumeration and benefits, and recruitment. The level of competencies of teachers in private schools were at a highest level with the mean level from highest to lowest as follows: self-improvement of teachers, teaching management, achievement motivation, teamwork, and teachers’ leadership; 2) The relationship of human resource management and competencies of teachers in private schools were positive at 0.947 with significant level of 0.01 (p< 0.01, r = 0.947); 3) The factors affecting competencies of teachers in private schools with the mean level from highest to lowest as follows: human resource planning, work evaluation, personnel development, and personnel relationship, respectively.